Patient understanding and experience of non-invasive imaging diagnostic techniques and the liver patient pathway - Andy McKay; Carlos Pantoja; Richard Hall; Sarah Matthews; Phil Spalding; Rajarshi Banerjee (SpringerOpen, 2021)
Abstract Background Clinical and patient-reported outcomes are positively affected when efforts to increase patient understanding of underlying diseases and foster patient participation are part of care pathways. The prevalence of liver diseases is increasing globally, and successful communication of results from liver diagnostic tests will be important for physicians to ensure patient engagement and encourage adherence to lifestyle changes and therapy. Here, we aimed to explore the impact of non-invasive liver tests on patient experience and patient comprehension of liver disease in chronic liver disease diagnostic pathways typically managed with liver biopsies. Results 101 participants diagnosed with a range of liver disease aetiologies (90 patients, 11 caregivers) underwent a multiparametric magnetic resonance imaging (MRI) test. A subset of 33 participants was subjected to transient elastography (TE) with FibroScan® in addition to multiparametric MRI. MRI results were analysed using LiverMultiScan™. Participants received results on their liver-health status followed by a semi-structured interview to assess the scan procedure experience, comprehension of the results, and experiences of liver disease. A subset of participants (N = 5) was also engaged in the design, execution, and thematic analysis of the interview transcripts of the study. Analysis of semi-structured interviews revealed: (1) Presentation and discussion of the LiverMultiScan visual report by a physician was an effective contributor to better patient experience and increased comprehension of liver disease. (2) Patients demonstrated preference for non-invasive tests over biopsy for management of liver disease. (3) Patients reported positive experiences with the MRI test during the path for liver disease management. Conclusions Patients presented with visual reports of liver test results developed increased understanding of liver disease care which may have contributed to an overall more positive experience. Patients reported that clinical information obtained through non-invasive methods and transmitted through visual reports contributed to clarity, understanding and overall increased satisfaction. We conclude that a shift toward non-invasive testing and visual reporting of clinical information (e.g. picture of liver with visual scale) when possible are likely to contribute to improved physician engagement with patients and lead to better outcomes in the management of chronic liver diseases. Plain English summary Evidence suggests that patient experience and understanding can affect several aspects of clinical care and patient well-being. In this study, 101 patients and patient caregivers affected by liver diseases were recruited to determine how patient experiences of liver disease were affected with the introduction of non-invasive evaluation of the liver with an MRI or ultrasound-based elastography. All 101 participants received an MRI followed by a LiverMultiScan report. 33 participants received an additional FibroScan and report. Following the reports, participants were interviewed and asked to reflect on factors which affected their experience of the procedure and the understanding of their results. We focused on factors related to the layout of the standardised report and the delivery of its results. The interviews were transcribed and analysed for common themes and patterns. Patients and patient advocacy groups were involved in the design and conduct of the study, and analysis of the interview transcripts. Here, we report the perception of patients and patient caregivers on the quality of care and diagnostic experience. Trial registration ClinicalTrials.gov identifier-NCT02877602.